Laser Equipment (СО) e-course - Lobankova, O. V. specialist in the field of lightning engineering engineer of Tomsk Polytechnic University 1990- (TPU Moodle, 2016)
The aim of the course is to provide advanced knowledge and basic understanding of the fundamental and applied aspects of physics and constructions of lasers, research methods with laser application. The considerable part of the course is devoted to studying of features of laser complexes. Constructions of lasers allow understanding more deeply the nature of laser parts. The processes of influence of laser radiation on materials are going to be studied. Characteristics of laser radiation are considered in this course. The main aim of the course at the initial stage of specialization is to present the most actual problems of laser physics and technology of laser treatment, for further student training and independent research work.